COMPARATIVE ANALYSIS OF THE SEMIOTICS OF DISSEMINATED PULMONARY TUBERCULOSIS AND EXOGENOUS ALLERGIC ALVEOLITIS IN ACCORDANCE WITH THE DATA OF COMPUTED TOMOGRAPHY - R. B. Amansakhedov; I. V. Limarova; A. V. Perfiliev; R. Yu. Abdullaev; A. T. Sigaev; A. E. Ergeshov (Вестник рентгенологии и радиологии)
Objective: to improve the differential diagnosis of disseminated pulmonary tuberculosis (DPT) and exogenous allergic alveolitis (EAA) via comparative investigation of their computed tomography (CT) semiotics and identification of the most informative diagnostic criteria. Material and methods. 70 patients, including 40 patients with DPT in a phase of infiltration and 30 patients with acute EAA, were studied using a Somatom Emotion 16 multi-slice spiral CT scanner (Siemens). All the patients underwent spiral scanning from the upper chest aperture to the costodiaphragmatic recesses with a high CT algorithm at 0.8-mm slice thickness and a 1.5-mm step. Results. Analysis of the spread of dissemination foci established that pathological changes were peribronchovascularly located in both nosological entities and characterized by a preponderance of septal and intrabronchial locations in DPT and by a centrilobular distribution in EAA. Centrilobular foci were more commonly poorly defined in EAA and mixed foci were observed in DPT. In the latter, peribronchovascular, centrilobular foci were revealed at a distance from the visceral pleura (the boundary of the deep and superficial lymphatic network, respectively) in 38% and more than half of the cases (62%) with the involvement of the visceral and parietal pleura; in EAA, the centrilobular foci were more often combined with the involvement of the visceral pleura in more than 92% of cases. The tree-in-bud sign was significantly more common in DPT. The latter was mostly characterized by apicocaudal regression of dissemination. In EAA, the foci were more frequently located asymmetrically. Monomorphic foci with destruction, as well as their polymorphism were seen in DPT; those without destruction were predominantly observed in EAA. CT ground glass and mosaic perfusion syndromes were significantly more often in EAA. In DPT, the visceral and parietal pleuras were involved in the process in 62% of cases and changes were also more common in the extrapleural fat. Conclusion. In addition to the peribronchovascular location of foci, the characteristic CT signs for DPT are a preponderance of intrabronchial and septal locations of foci, their apicocaudal regression, the presence of the CT tree-in-bud sign, and thickened extrapleural fat. EAA showed a prevalence of asymmetrical foci with centrilobular location with the involvement of the visceral pleura into the process, with the presence of CT ground glass and mosaic perfusion syndromes, as well as the bronchial lumen visualized in the peripheral segments of the lung.